Adaptation to Cold Affects the Dimensions of Adrenal Gland Zones in Hibernating and Non-hibernating Animals - Shylo, Oleksandr V.; Lutsenko, Dmytro G.; Karibian, Ihor M.; Lomako, Viktoria V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 019–023